Suxiao Jiuxin pill promotes exosome secretion from mouse cardiac mesenchymal stem cells in vitro - RUAN Xiao-fen; JU Cheng-wei; SHEN Yan; LIU Yu-tao; KIM Il-man; YU Hong; WEINTRAUB Neal; WANG Xiao-long; TANG Yaoliang (Acta Pharmacologica Sinica, 2018)
Abstract Cardiac mesenchymal stem cells (C-MSCs) are endogenous cardiac stromal cells that play a role in heart repair after injury. C-MSCderived exosomes (Exo) have shown protective effects against apoptosis induced by acute myocardial ischemia/reperfusion. Suxiao Jiuxin pill (SJP) is a traditional Chinese medicine (TCM) formula used in China for the treatment of acute myocardial ischemia, which contains tetramethylpyrazine (TMP) and borneol (BOR) as major components. In this study, we investigated whether SJP treatment affected exosome release from C-MSCs in vitro. C-MSCs prepared from mice were treated with SJP (62.5 μg/mL), TMP (25 μg/mL) or BOR (15 μg/mL). Using an acetylcholinesterase activity assay, we found that both SJP and TMP treatment significantly increased exosome secretion compared to the control ethanol treatment. The neutral sphingomyelinase 2 (nSMase2) pathway was important in exosome formation and packaging. But neither the level of nSMase2 mRNA nor the level of protein changed following SJP, TMP or BOR treatment, suggesting that SJP stimulated exosome release via an nSMase2-independent pathway. The Rab27a and Rab27b GTPases controlled different steps of the exosome secretion pathway. We showed that SJP treatment significantly increased the protein levels of Rab27a, SYTL4 (Rab27a effector) and Rab27b compared with the control treatment. SJP treatment also significantly upregulated the mRNA level of Rab27b, rather than Rab27a. Moreover, SJP-induced increase of C-MSC-exosome release was inhibited by Rab27b knockdown, suggesting that SJP promotes exosome secretion from C-MSCs via a GTPase-dependent pathway. This study reveals a novel mechanism for SJP in modulating cardiac homeostasis.